Barack Obama and the Closure of Guantanamo Prison, 2009 - Toufouti, Youcef (Journal of Human Sciences, 2022)
As it was the most notorious prison in the world, American president Barack Obama believed that the closure of Guantanamo prison within only one year after taking office would be an easy thing to do. But it was not the case. Obama’s attempt to fulfill his promise proved to be impossible, and it was really surprising to the newly elected president that there were many factors that have made it impossible for him to keep his promise; therefore, this article presents an analysis of the main reasons behind Obama’s failure to carry out his pledge of closing Guantanamo.